Drought exposure as a risk factor for child undernutrition in low- and middle-income countries: a systematic review and assessment of empirical evidence - Belesova, Kristine; Agabiirwe, Caroline Noel; Zou, Margaret; Phalkey, Revati; Wilkinson, Paul (Environment international, 2019)
Background - Droughts affect around 52 million people globally each year, a figure that is likely to increase under climate change. - Objectives - To assess the strength of empirical evidence on drought exposure as a risk factor for undernutrition in children <5years of age in low- and middle-income countries (LMICs). - Methods - Systematic review of observational studies published between 1990 and 2018 in English and reporting undernutrition outcomes in children <5years of age in relation to droughts in LMICs. The search was performed in the Global Health, Medline, Embase, and Scopus databases. We assessed the strength of evidence following the Navigation Guide. - Results - 27 studies met our inclusion criteria. 12 reported prevalence estimates in drought-affected conditions without comparison to unaffected conditions. These showed high prevalence of chronic and mixed undernutrition and poor to critical levels of acute undernutrition. Only two studies were judged to have low risk of bias. Overall, the strength of evidence of drought as a risk factor was found to be limited, but the two studies with low risk of bias suggested positive associations of drought exposure with children being underweight and having anaemia. - Conclusion - Published evidence suggests high levels of all types of child undernutrition in drought-affected populations in low-income settings, but the extent to which these levels are attributable to drought has not been clearly quantified and may be context specific. This review offers suggestions for enhancing the quality of future studies to strengthen evidence on the potential magnitude, timing, and modifying factors of drought impacts.